Legal Challenges and the Strategic Role of PPAT in Inheritance of Uncertified Land with NPOP-Based Tax Obligations in Indonesia - Nur Fikri, Mohamad; Maulina, Nia (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2026)
Land ownership has a central role in the legal, economic, and social systems of Indonesia. The transfer of land rights through inheritance is a common legal event that often occurs when the owner of land passes away and the property is transferred to heirs according to applicable inheritance law. However, in practice many inherited lands in Indonesia are not yet registered or certified. This situation creates legal uncertainty, particularly when the transfer of rights is associated with taxation obligations related to the acquisition value of the tax object (Nilai Perolehan Objek Pajak/NPOP). In this context, the role of the Land Deed Official (Pejabat Pembuat Akta Tanah/PPAT) becomes crucial in ensuring the legality and validity of the inheritance process. This study aims to analyze the role of PPAT in handling inheritance cases involving uncertified land that has a taxable acquisition value. The research uses a normative legal research method with statutory and conceptual approaches. The findings indicate that PPAT plays an important role in verifying ownership documents, preparing authentic deeds, and ensuring compliance with taxation regulations related to land transfer. However, uncertified land often creates administrative and legal challenges in determining ownership history and calculating the acquisition value of the tax object. Therefore, strengthening legal regulations, improving land registration systems, and increasing public awareness of land certification are necessary to ensure legal certainty and effective land administration.